Effectiveness of a guidance program according to Enneagram model to strengthen psychological immunity among 100-200m runners in Wasit Education Directorate team - Ali Muayyad Yahya Hamad (Journal of Applied Movement and Sport Science, 2026)
Background Athletics is one of sports that is characterized by intense competition due to its nature in which competitor exerts maximum physical and psychological effort, and these variables have multiple effects on achievement. Objectives This study aimed to develop a guidance program based on Enneagram for 100m and 200m runners from student teams participating in Wasit Education Directorate championships. research then sought to determine effectiveness of this program in strengthening psychological resilience of these runners. Methods Regarding research methodology, researcher used a descriptive approach. Survey method and correlational relationships were chosen to suit nature of problem and objectives of current study. Research population and sample were defined as middle school students participating in competitions organized by Sports and Scouting Activities Department of Wasit General Directorate of Education. Total number of students was 72, of whom 22 were randomly selected as main sample and 40 as application sample. After defining research variables, researcher developed a psychological immunity scale and then presented it to a group of experts and specialists in field of psychology to determine suitability of items to five dimensions of scale, as well as their clarity for respondent. After researcher conducted statistical tests for scale's validity, reliability, discriminatory power, and internal consistency, scale was finalized for use. Afterwards, researcher conducted a pilot study on a sample of 10 runners to confirm validity of scale. Then conducted main experiment, as it applied scale to sample, which amounted to 40 participating students as runners for that event. After converting responses into scores and using statistical methods, degree of psychological resilience possessed by sample was determined. Subsequently, a guidance program was initiated to enhance their psychological resilience, based on Enneagram model. This model, in turn, contributed to analyzing personality type of each individual in sample through a Thematic Apperception Test. Results Results showed that sample exhibited weaknesses in psychological immunity, emotional maturity, psychological well-being, positive thinking, and coping mechanisms for pressures they experience during competitions and training. Conclusion Among most prominent recommendations mentioned by researcher Physical education teachers were Guidance program lasted for eight weeks, with three sessions per week, focusing on how athletes can protect themselves from pressures and difficulties they encounter. After guidance sessions concluded, sample demonstrated their engagement with program's content.